2008
DOI: 10.1681/asn.2007101098
|View full text |Cite
|
Sign up to set email alerts
|

A Common RET Variant Is Associated with Reduced Newborn Kidney Size and Function

Abstract: Congenital nephron number varies five-fold among normal humans, and individuals at the lower end of this range may have an increased lifetime risk for essential hypertension or renal insufficiency; however, the mechanisms that determine nephron number are unknown. This study tested the hypothesis that common hypomorphic variants of the RET gene, which encodes a tyrosine kinase receptor critical for renal branching morphogenesis, might account for subtle renal hypoplasia in some normal newborns. A common single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 33 publications
6
115
1
Order By: Relevance
“…This population has been shown to have kidneys with fewer nephrons and to more frequently develop hypertension, proteinuria, and chronic renal failure (18,19). Similarly, Zhang et al (10) have shown that a common variant of the RET gene is associated with reduced KS in newborns and in the number of glomeruli, as measured in autopsy specimens of children that died before the age of 3 months.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This population has been shown to have kidneys with fewer nephrons and to more frequently develop hypertension, proteinuria, and chronic renal failure (18,19). Similarly, Zhang et al (10) have shown that a common variant of the RET gene is associated with reduced KS in newborns and in the number of glomeruli, as measured in autopsy specimens of children that died before the age of 3 months.…”
Section: Discussionmentioning
confidence: 95%
“…Autopsy data, however, suggest that subjects with fewer nephrons tend to have smaller kidneys that contain hypertrophic glomeruli (9). A direct correlation between kidney weight and nephron number has been also reported in infants (10). In this study, we hypothesized that, in the normal pediatric population, part of the physiologic variance in BP and in GFR, as assessed by the serum creatinine, is related to differences in renal size.…”
Section: Introductionmentioning
confidence: 84%
“…Nephrogenesis in humans ends at around 36 weeks of gestation, after which no new nephrons can form 16 . In the Monash series, nephron number in 15 infants who died before the age of 3 months ranged 4.5-fold, from 246,181 to 1,106,062, suggesting that much of the variation in adult human nephron number is determined before birth 18 .…”
Section: Nephron Number In Humansmentioning
confidence: 99%
“…Search for common polymorphisms in several genes known to participate in kidney development have shown correlations between altered gene transcription and newborn kidney size, which is proportional to nephron number (Table 1) 18 . These studies have been conducted in primarily Caucasian populations, therefore implications in other populations need to be investigated 18,46,47 . The molecular mechanisms regulating nephrogenesis are expertly reviewed elsewhere 48 .…”
Section: Developmental Determinants Of Low Nephron Numbermentioning
confidence: 99%
See 1 more Smart Citation